2013
DOI: 10.1002/ajim.22133
|View full text |Cite
|
Sign up to set email alerts
|

Personal service assistance: Musculoskeletal disorders and injuries in consumer‐directed home care

Abstract: Background: Like other types of home care for disabled or elderly adults, consumer-directed Personal Assistance Services may present multi-factorial risks for work-related musculoskeletal disorders and injuries (WRMSDs). Methods:Using telephone survey data (n=855, including 474 family members), we compared providers who experienced WRMSDs in the previous year to those who did not to identify functional, temporal, physical and social risk factors for transient and chronic conditions. Results:Longer work experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The survey included demographic and work environment questions and validated measures to assess provider health, and work injuries and musculoskeletal disorders [17] .…”
Section: Instrumentmentioning
confidence: 99%
“…The survey included demographic and work environment questions and validated measures to assess provider health, and work injuries and musculoskeletal disorders [17] .…”
Section: Instrumentmentioning
confidence: 99%
“…This could contribute to risks for both patients and caregivers when visits were shortened due to concerns about abuse, physically challenging tasks (moving and handling), missing/inadequate equipment and consumables (Galinsky et al, 2010). There could also be pressure from the patient (and family) to deliver care when the caregiver did not feel that they had the appropriate knowledge, training and skills (Faucett et al, 2013;Munck et al, 2011). Caregivers could feel very isolated and unsupported, especially if the equipment and consumables needed to provide the care were missing, inadequate or had changed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence was found that identified physical risks associated with inadequate and missing equipment, e.g. lifting or bathing equipment which was the incorrect size and/or weight capacity for the patient (strong evidence: Hale & Piggot, 2005;moderate evidence: Craven et al, 2012;Faucett et al, 2013;Leiss, 2012;Pohjonen et al, 1998;Simon et al, 2008;Sims-Gould et al, 2013) and a lack of support for maintenance and training in medical devices (moderate evidence: Munck et al, 2011).…”
Section: Artefacts (Equipment and Technology)mentioning
confidence: 99%
“…Brief induction classroom training sessions in the Australian home care sector are a common method of orientating new HCWs to their roles, conveying information such as safe manual handling, managing challenging behaviours, infection control and other important safety procedures. Classroom-based manual handling training, specifically, has been largely unsuccessful in reducing the alarming rates of musculoskeletal (predominantly back) injuries amongst these workers (Faucett, Kang & Newcomer, 2013;Markkanen et al, 2014). While larger organisations may offer more systematic, mandated training programs, smaller ones tend to provide more ad-hoc and fewer hours of training, citing financial constraints or workers "already skilled enough" as reasons why this is the case (Baldock & Mulligan, 2000).…”
Section: Working and Learning In Australian Home Carementioning
confidence: 99%